In Vitro Schistosomicidal Activities of the Leaf Extracts from Casearia sylvestris Varieties - Carvalho, Flávio A. [UNESP]; da Silva, Breno C.; Oda, Fernando B. [UNESP]; Junior, Júlio C. P. [UNESP]; Crevelin, Eduardo J.; Crotti, Antônio E. M.; Caldas, Lizandra G. M.; dos Santos, André G. [UNESP] (Wiley, 2022)
Schistosomiasis, a tropical disease caused by flatworms, may affect the liver, spleen, bladder, and intestine. Casearia sylvestris Swartz, a medicinal plant, displays antiprotozoal, antimicrobial, antifungal, and antiulcer activities. We have evaluated the in vitro schistosomicidal activity of two C. sylvestris varieties against Schistosoma mansoni adult worms at concentrations between 12.5 and 200 μg/mL. At 100 and 200 μg/mL, the ethanolic C. sylvestris var. sylvestris leaf extract enriched in casearin-like diterpenes eliminated 100 % of the parasites after incubation for 72 h and 48 h, respectively, whilst the same extract at 200 μg/mL eliminated 96 %, 100 %, and 100 % of the parasites after incubation for 24, 48, and 72 h, respectively. On the other hand, the hydroalcoholic C. sylvestris var. lingua leaf extract at 200 μg/mL eliminated 60.4 and 66.7 % of the parasites after incubation for 48 and 72 h, respectively. The presence of casearin-like diterpenes and glycosylated flavonoids was confirmed based on chromatographic techniques and mass spectrometry data.
Keywords: Casearia sylvestris; casearin; flavonoids; neglected diseases; Schistosoma mansoni